2014
DOI: 10.1136/bjsports-2014-093494.135
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of the Nordic Hamstring Exercise on Hamstring Injuries in Amateur Soccer Players: A Randomized Controlled Trial

Abstract: Background Hamstring injuries are the most common muscle injuries in male amateur soccer. Eccentric strength of the hamstrings is recognized as an important modifiable risk factor, leading to the development of preventive exercises such as the Nordic Hamstring Exercise. Objective This study aims to investigate the preventive effect of the Nordic Hamstring Exercise on the incidence and severity of hamstring injuries in male amateur soccer players. Design Cluster-randomized controlled trial with soccer teams a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
194
2
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(228 citation statements)
references
References 0 publications
10
194
2
22
Order By: Relevance
“…We have provided sEMG evidence to suggest that, during eccentric contractions, hip-extension exercise more selectively activates the lateral hamstrings while knee flexion-oriented exercises preferentially recruit the medial hamstrings. However, despite being the least selective activator of the BF, the Nordic still elicited higher levels of BF nEMG during eccentric actions than any other exercise which may help to explain how it confers HSI-preventive benefits 15 16 18. Our fMRI investigation largely confirmed our initial sEMG observations, showing that, relative to the semitendinosus, the BF LongHead was ∼4 times more active in hip extension than in the Nordic exercise.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We have provided sEMG evidence to suggest that, during eccentric contractions, hip-extension exercise more selectively activates the lateral hamstrings while knee flexion-oriented exercises preferentially recruit the medial hamstrings. However, despite being the least selective activator of the BF, the Nordic still elicited higher levels of BF nEMG during eccentric actions than any other exercise which may help to explain how it confers HSI-preventive benefits 15 16 18. Our fMRI investigation largely confirmed our initial sEMG observations, showing that, relative to the semitendinosus, the BF LongHead was ∼4 times more active in hip extension than in the Nordic exercise.…”
Section: Discussionsupporting
confidence: 72%
“…The Nordic hamstring exercise is effective15 16 18 in reducing HSIs in soccer players as long as compliance is adequate 37 38. However, we11 and others22 have previously reported that the Nordic preferentially activates the semitendinosus, and this might be interpreted as evidence that the exercise is suboptimal to protection against running-related strain injury which predominantly effects the BF LongHead .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, the efficacy of the NH programme on hamstring injury risk is well documented,1 28 and confirmed in a recent study on male Dutch amateur players documenting a 72% reduction in the risk for hamstring injuries 40. The NH exercise addresses the mechanism of injury, believed to be excessive maximal eccentric loading,23–25 as well as one key risk factor, eccentric strength.…”
Section: Discussionmentioning
confidence: 96%
“…Neuromuscular coordination exercises are used in the FMS rotary stability movement. Sideways bench item exercises and bench items to strengthen thigh muscles, which can help the participant to properly perform the FMS active straight leg raise movement (26,27).…”
Section: Discussionmentioning
confidence: 99%